AN EXAMPLE OF WIND TURBINE STRUCTURE - Marija Jelčić (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2020)
The purpose of this paper is to develop structural design of a wind turbine foundation and tower. The structural modeling was performed in program Tower 7. All structural elements are calculated according to the applicable regulations of Eurocode and National Annexes. The structure consists of a steel tower calculated in segments and a reinforced concrete foundation made in a monolithic design. The wind turbine tower is a steel tubular tower, while the foundation is made of reinforced concrete in a circular shape.